A low profile RF shielding FSS with enhanced ultrawide bandwidth range and angular stability. Issue 9 (24th May 2022) - Prasad, Pratyancha; Singh, Shiva Nand; Kumar, Akhilesh
Abstract: This article describes a frequency selective surface (FSS) for shielding with an improved angular stability over a wide frequency range. The proposed unit design consists of a circular ring in a square element, two cross dipoles, and a T‐type slotted structure printed of size 0.052 lambda0  × 0.052 lambda0 on a layer of FR4 substrate having a thickness of 0.0075 lambda0 . Here lambda0 is the free‐space wavelength of lower cut‐off frequency. It has improved the bandwidth range from 2.84 GHz to more than 20 GHz enough to provide effective shielding against the entire ultra‐wideband (UWB) range, as well as the X– and Ku–bands. Up to 75 degrees of oblique incidence, the proposed design is polarisation independent and angularly stable. The structure is full wave simulated and an equivalent circuit model is realised. The findings are validated through the use of a fabricated prototype. The applications of shielding are in reducing electromagnetic interference in civil and military applications as well as improving the gain of UWB patch antennas.